Pengaruh Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan (Studi Pada Pegawai Dinas Pemadam Kebakaran Dan Penyelamatan Kabupaten Cirebon) - Asep Sumarsana (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The purposes of this study are: 1) To analyze how work discipline, work motivation and performance of employees of the Cirebon Regency Fire and Rescue Service are. 2) To find out whether there is an effect of work discipline on the performance of the employees of the Cirebon Regency Fire and Rescue Service. 3) To find out whether there is an effect of work motivation on the performance of the employees of the Cirebon Regency Fire and Rescue Service. 4) To find out whether there is an influence of work discipline and work motivation on the performance of the employees of the Cirebon Regency Fire and Rescue Service. The method in this study uses a causal associative approach. The population in this study were 40 employees of the Cirebon Regency Fire and Rescue Service, all of which will be used as sample subjects in this study. Research analysis with multiple linear regression. Data processing is assisted by the SPSS program. The results of this study conclude: 1) Discipline has an effect on employee performance. If discipline is improved, employee performance will also increase. 2) Work motivation has an effect on employee performance. The more work motivation given to employees, the employee's performance will increase. 3) Discipline and work motivation together affect employee performance. The effect together is 75.3%, the rest is influenced by other variables.